2009
DOI: 10.1515/hf.2009.094
|View full text |Cite
|
Sign up to set email alerts
|

Orientation of the wood polymers in the cell wall of spruce wood fibres

Abstract: The mechanical and physical properties of wood fibres depend to a large extent on the orientation of the polymers, mainly the cellulose microfibrils, within the supramolecular structure of the cell wall. Under moist conditions, the arrangement within the polymer matrix may play a dominant role for mechanical properties in general and, especially, in the transverse direction. In this context, it is of special interest to determine the orientation of glucomannan and xylan, being the essential components of softw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
104
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 9 publications
6
104
0
Order By: Relevance
“…Furthermore the orientation of cell wall polymers can be elucidated by polarised FT-IR measurements. In spruce glucomannan and xylan appear to have a parallel orientation with regard to the orientation of cellulose and, in all probability, an almost parallel orientation with regard to the fibre axis [74]. The first evidence for lignin orientation within native wood cell walls was revealed by Raman microprobe studies [75] and later confirmed in the secondary wall of tracheids fibres of thermomechanical pulp by FT-IR [70].…”
Section: Introductionmentioning
confidence: 94%
“…Furthermore the orientation of cell wall polymers can be elucidated by polarised FT-IR measurements. In spruce glucomannan and xylan appear to have a parallel orientation with regard to the orientation of cellulose and, in all probability, an almost parallel orientation with regard to the fibre axis [74]. The first evidence for lignin orientation within native wood cell walls was revealed by Raman microprobe studies [75] and later confirmed in the secondary wall of tracheids fibres of thermomechanical pulp by FT-IR [70].…”
Section: Introductionmentioning
confidence: 94%
“…FTIR imaging has been found to be a remarkable tool for biological and materials analysis. It can be used extensively to investigate the chemical composition of stem [83][84][85] and cell wall structure [86] of natural fibres, and natural fibre composites [87].…”
Section: Morphologies Of Natural Fibres By Using Ftirmentioning
confidence: 99%
“…In the analysis of spectra, this has to be taken into account and one can even extract orientational information (Gierlinger et al 2010). By inserting a polarizer in the beam path of the IR microscope, this method can also be used to extract information on the orientation of the wood polymers (Stevanic and Salmén 2009). …”
Section: Principles Of Infrared Raman and Uv Microspectroscopy With mentioning
confidence: 99%
“…Therefore, care has to be taken to proper sample and laser alignment and not to mix up changes in content with changes in orientation (Gierlinger and Schwanninger 2006). Lignin, which is less oriented than cellulose within the wood cell wall (Stevanic and Salmén 2009;Gierlinger et al 2010), can be mapped by having marker bands not overlapping with contributions from cellulose and hemicelluloses. Even small amounts in a very thin layer towards the lumen of G-layer of poplar tension wood could be visualised (Agarwal 2006).…”
Section: Uv-vis Spectra Of Lignin and Other Ring Structuresmentioning
confidence: 99%
See 1 more Smart Citation